On the development, optical properties and thermal performance of cool colored coatings for the urban environment - Synnefa, A.; Santamouris, M.; Apostolakis, K. (Solar energy, 2007)
This paper reports the measured solar spectral properties and the thermal performance of 10 prototype cool colored coatings, developed at the National and Kapodistrian University of Athens, using near-infrared reflective color pigments in comparison to color-matched, conventionally pigmented coatings. These coatings are developed to be used in the urban environment to fight the heat island effect. The spectral reflectance and the infrared emittance were measured and the solar reflectance of the samples was calculated. The surface temperature of the coatings when applied to concrete tiles was monitored, using surface temperature sensors and a data logging system, on 24 h basis from August to December 2005 in an effort to investigate the ability of the cool colored coatings to maintain lower surface temperatures than conventionally pigmented color-matched coatings. The data obtained has been extensively analysed and indicate significant success in the development of these cool colored coatings. It was found that all the coatings containing infrared reflective pigments have solar reflectance values higher than those of standard coatings. Furthermore, it was demonstrated that cool colored coatings maintain lower surface temperatures than color-matched conventionally pigmented coatings. This temperature difference is mainly due to differences in solar reflectance. These cool colored coatings can be used on buildings (roofs and walls) and other surfaces in the urban environment. Thus, at building scale, the use of cool colored coatings with increased solar reflectance can improve building comfort and reduce cooling energy use, and at city city-scale it can contribute to the reduction of the air temperature due to the heat-transfer phenomena and therefore improve outdoor thermal comfort and reduce the heat-island effect.